Effect Of Use Menstrual Cup To Personal Hygiene And Genital Inflammation : Systematic Literature Review - Eka Septi Adelia Putri; Izzati Dwi; Pudji Lestari (Faculty of Medicine, Universitas Andalas, 2021)
Backgrounds: Poor personal hygiene factors and frequency of changing sanitary napkins make genital becomes more moist and susceptible to bacterial growth. (Sari, 2012). The alternative choice of the menstrual cup is considered the best medium for collecting menstrual blood because it can minimize fishy odors and the emergence of infections, irritations, and rashes (Beksinska et al., 2015).Purpose: Describe the menstrual cup affect on personal hygiene and genital inflammation. Method: This study used a systematic review of articles in the Scopus, Pubmed, Science Direct, Proquest, and EBSCOhost CHINAHL. Twelve articles that met the inclusion and exclusion criteria were included as samples for future review. The results regarding the factors causing late referral are explained in the narrative. Result: Participants had good habits in personal hygiene when using menstrual cups (6 articles), participants felt the benefits of menstrual cups (5 articles), it was found that genital inflammation in low prevalence, but also the majority of participants felt the benefits of menstrual cups (5 articles). Conclusion: Generally participant had a good habit, although there is some different personal hygiene method. The menstrual cup is a kind of safe menstrual sanitary with low risk of health problems, so it can be a choice for women.